تأثير تمرينات بمقاومات مختلفة لتطوير القدرة الإنفجارية ودقة التهديف بالقفز للاعبين المتقدمين بكرة السلة - نوري, محمد صالح محمد; أمين, ندى محمد; جارو, شيرزاد محمد (Sulaimani Journal for Humanities, 2018)
Explosive ability is one of the elements of the physical preparation of advanced basketball players. If not, they contribute actively to the development of muscle level and performance and the skill level of the basketball player, including scoring by jumping inside and outside the arc of three points as an effective weapon to win the game. The importance of research is through the emphasis on the application of explosive power training of the arms and legs using different resistors and according to the principle of gradation and investment to develop scoring by jumping from inside and outside the arc of three points in the basketball. The problem of the research is the lack of the use of different resistors in explosive power exercises aimed at increasing the resistance on the player and invest this gradient in the resistance is optimal by near and after the player of the goal, which reflected negatively on the technology of scoring jumping from inside and outside the arc of three points for players advanced basketball. The aim of the research is to develop different resistance exercises for the basketball players and to identify their effect on the development of the explosive ability and accuracy of the jumping score for the players who submit the basketball. The imposition of the research indicates that there are statistically significant differences between the tribal and remote tests in the explosive ability and the accuracy of the jumping score for the advanced basketball players. The research was conducted on the players of Al-Adhamiya basketball club participating in the league of Baghdad clubs basketball with the participation of 6 teams and the sample number (12) of the total (72) player and by (16.66%), the following tests were conducted (Explosive force test for arms, Explosive force test for legs, The jump test from the outside of the arc of the three points, The jump test from the front to the left of the free throw line and then the semi-circular move to the center and the right). The search continued for the period from 10/1/2017 until 11/3/2017, as well as the appropriate statistical means. The researchers concluded that exercises with different resistances contributed to the development of the explosive power of the arms and legs and thus improved the scoring by jumping from inside and outside the arc of the three points for the advanced basketball players, and the exercise contributed to the economy in the amount of strength of the muscles by improving the technique of performance and increasing scoring accuracy. The researchers recommend the need for gradual use of macrophages in all physical exercises and the work of muscles participating in the performance and the amount of strength and muscle need during performance and the manner of performance with the way the performance of scoring by jumping basketball as much as possible by allocating sufficient time in the training modules.